2018
DOI: 10.4314/sajas.v48i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of carcass characteristics and fat deposition of Merino, South African Mutton Merino and Dorper lambs housed in a feedlot

Abstract: The objective of this study was to determine the effect of time spent in a feedlot on the size of the various fat depots and the distribution of the main tissues (muscle, bone, and fat) of three common South African sheep breeds. Lambs were supplied with a balanced diet (16% protein, 10 MJ ME/kg feed) ad libitum and had free access to water. Lambs from each breed were divided into six groups, which were slaughtered at 21-day intervals until a production period of 105 days had been reached. During carcass dress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
11
1
1
Order By: Relevance
“…Intact rams also presented higher growth rates and were leaner than castrated lambs at slaughter (Schanbacher et al, 1980), whereas the fat depths of ewe lambs and wethers were similar when slaughtered at the same live weight (Dimsoski et al, 1999). Brand et al (2018) found higher rates of fat deposition in Dorper lambs than in SAMM lambs, which were in turn higher than those of Merino lambs. Cloete et al (2012) observed that the subcutaneous fat depths of Dormer and SAMM carcasses were greater than those of Dohne Merino and Merino carcasses.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Intact rams also presented higher growth rates and were leaner than castrated lambs at slaughter (Schanbacher et al, 1980), whereas the fat depths of ewe lambs and wethers were similar when slaughtered at the same live weight (Dimsoski et al, 1999). Brand et al (2018) found higher rates of fat deposition in Dorper lambs than in SAMM lambs, which were in turn higher than those of Merino lambs. Cloete et al (2012) observed that the subcutaneous fat depths of Dormer and SAMM carcasses were greater than those of Dohne Merino and Merino carcasses.…”
Section: Resultsmentioning
confidence: 79%
“…R. 863, 2006). Feedlot operators tend to be prejudiced against finishing early maturing breeds, because they deposit fat at an earlier age and therefore have to be slaughtered at a lower live weight (Brand et al, 2018), thereby reducing the income per carcass. However, in harsher climatic regions, in which the earlier maturing Dorper, Meatmaster, and Namaqua Afrikaner are used predominantly and demand for lamb is high, operators may decide to enter these lambs in the feedlot.…”
Section: Introductionmentioning
confidence: 99%
“…Breeds developed from indigenous fat-tailed or fat-rump breeds tend to be early maturing and tend to deposit fat at an earlier age, as is the case with the Dorper, Meatmaster, and Namaqua breeds. These breeds also show differences in fat partitioning between the various fat depots, as well as the distribution of subcutaneous fat [9,17]. Breeds also vary in their growth potential in terms of frame size and growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…When considering that lambs of different breeds start to deposit fat at different stages as well as exhibit different growth capacities, it is important to implement precision finishing in maintaining production sustainability. Early maturing breeds deposit fat at an earlier stage and must, therefore, be slaughtered at a lighter live weight compared to later-maturing breeds for carcasses to obtain the same classification [9]. With the differences in slaughter weight, it is possible that the different breeds will not only differ in terms of carcass size and shape but could possibly differ in terms of meat quality characteristics, as it is not clear from previous studies [3,4] whether the effects of different breeds are accounted for by the quality descriptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation